Impact of augmented renal clearance on the pharmacokinetics of linezolid: Advantages of continuous infusion from a pharmacokinetic/pharmacodynamic perspective. (April 2020) - Barrasa, Helena; Soraluce, Amaia; Usón, Elena; Sainz, Javier; Martín, Alejandro; Sánchez-Izquierdo, José Ángel; Maynar, Javier; Rodríguez-Gascón, Alicia; Isla, Arantxazu
Highlights: Augmented renal clearance (ARC) significantly increases linezolid clearance. ARC leads to a high risk of suboptimal linezolid exposure at a dose of 600 mg every 12 h. Continuous infusion increases the probability of attaining the pharmacokinetic/pharmacodynamic target. In patients with ARC, continuous infusion of 75 mg/h ensures concentrations ≥2 mg/ml. Therapeutic drug monitoring may help to optimize linezolid dosing. Abstract: Objectives: The aim of this study was to assess the influence of renal function, in particular the presence of augmented renal clearance (ARC), on the pharmacokinetics of linezolid in critically ill patients. The effect of continuous infusion on the probability of therapeutic success from a pharmacokinetic/pharmacodynamic (PK/PD) perspective was also evaluated. Methods: Seventeen patients received linezolid (600 mg every 12 h) as a 30-min infusion and 26 as a continuous infusion (50 mg/h). The PK parameters were calculated and the probability of PK/PD target attainment (PTA) was estimated by Monte Carlo simulation (MCS) for different doses administered by intermittent (600 mg every 12 h or 600 mg every 8 h) or continuous infusion (50 mg/h or 75 mg/h). Results: In patients without ARC, the standard dose was adequate to attain the PK/PD target. However, linezolid clearance was significantly higher in ARC patients, leading to sub-therapeutic concentrations. Continuous infusion (50 mg/h) provided concentrations ≥2 mg/l in 70% of the ARC patients. MCS revealed that concentrations ≥2 mg/l would be reached in >90% of patients receiving 75 mg/h. Conclusions: ARC increases linezolid clearance and leads to a high risk of underexposure with the standard dose. Continuous infusion increases the PTA, but an infusion rate of 75 mg/h should be considered to ensure concentrations ≥2 mg/ml.